Can a Left Ventricular Assist Device in Individuals with Advanced Systolic Heart Failure Improve or Reverse Frailty?. Issue 11 (21st September 2017) - Maurer, Mathew S.; Horn, Evelyn; Reyentovich, Alex; Dickson, Victoria Vaughan; Pinney, Sean; Goldwater, Deena; Goldstein, Nathan E.; Jimenez, Omar; Teruya, Sergio; Goldsmith, Jeff; Helmke, Stephen; Yuzefpolskaya, Melana; et al.
Abstract : Background/Objectives: Frailty, characterized by low physiological reserves, is strongly associated with vulnerability to adverse outcomes. Features of frailty overlap with those of advanced heart failure, making a distinction between them difficult. We sought to determine whether implantation of a left ventricular assist device (LVAD) would decrease frailty. Design: Prospective, cohort study. Setting: Five academic medical centers. Participants: Frail individuals (N = 29; mean age 70.6 ± 5.5, 72.4% male). Measurements: Frailty, defined as having 3 or more of the Fried frailty criteria, was assessed before LVAD implantation and 1, 3, and 6 months after implantation. Other domains assessed included quality of life, using the Kansas City Cardiomyopathy Questionnaire; mood, using the Patient Health Questionnaire; and cognitive function, using the Trail‐Making Test Part B. Results: After 6 months, three subjects had died, and one had undergone a heart transplant; of 19 subjects with serial frailty measures, the average number of frailty criteria decreased from 3.9 ± 0.9 at baseline to 2.8 ± 1.4 at 6 months ( P = .003). Improvements were observed after 3 to 6 months of LVAD support, although 10 (52.6%) participants still had 3 or more Fried criteria, and all subjects had at least one at 6 months. Changes in frailty were associated with improvement in QOL but not with changes in mood or cognition. Higher estimated glomerular filtration rate at baseline was independently associated with a decrease in frailty. Conclusion: Frailty decreased in approximately half of older adults with advanced heart failure after 6 months of LVAD support. Strategies to enhance frailty reversal in this population are worthy of additional study.